2023
DOI: 10.1021/acs.jmedchem.2c02045
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of LL-K8-22: A Selective, Durable, and Small-Molecule Degrader of the CDK8-Cyclin C Complex

Abstract: The CDK8−cyclin C complex is an important anti-tumor target, but unlike CDK8, cyclin C remains undruggable. Modulators regulating cyclin C activity directly are still under development. Here, a series of hydrophobic tagging-based degraders of the CDK8−cyclin C complex were designed, synthesized, and evaluated to identify the first dual degrader, LL-K8-22, which induced selective and synchronous degradation of CDK8 and cyclin C. Proteomic and immunoblot studies exhibited that LL-K8-22 significantly degraded CDK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…90 Very recently, on the basis of the similar hydrophobic tagging strategy, Luo et al designed CDK8-cyclin C degraders and successfully degraded the undruggable target cyclin C and enhanced antitumor potency (Table 1). 95 Overall, these results indicated that menthoxyacetyl may be a useful pharmacological tool for investigating the unrecognized functions of complex proteins.…”
Section: Menthoxyacetyl-triggered Synchronous Degradation Of Cyclin D...mentioning
confidence: 84%
“…90 Very recently, on the basis of the similar hydrophobic tagging strategy, Luo et al designed CDK8-cyclin C degraders and successfully degraded the undruggable target cyclin C and enhanced antitumor potency (Table 1). 95 Overall, these results indicated that menthoxyacetyl may be a useful pharmacological tool for investigating the unrecognized functions of complex proteins.…”
Section: Menthoxyacetyl-triggered Synchronous Degradation Of Cyclin D...mentioning
confidence: 84%
“…The DIA method eliminates the need for sample labeling, simplifies the workflow, and avoids additional expenses associated with the purchase or synthesis of labeling reagents. We pioneered to apply DIA-MS to PROTAC research, achieving quicker and more flexible processing of multiple samples than that with isobaric labeling quantitative analysis in customized experimental designs. …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, researchers used MS-based proteomics to determine the efficacy of PROTAC degraders with a single condition further with a series of treatment time points or doses. They mainly focused on the degradation of target proteins and differentially expressed proteins (DEPs) proteome-wide. ,, The limited proteomic data analysis is insufficient to understand the PROTAC efficacy and sensitivity. In this study, we applied DIA-based MS to multidimensional proteomic profiling of PROTAC, named “DIA-MPP,” for in-depth and comprehensive proteome profiling with multiple conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The HyT technique has proven to be highly efficient in its ability to specifically dismantle multiple targets, including the AR, [47] Her3, [48] Tau, [49] EZH2, [50] ALK, [51] CDK9, [52] CDK8, [53] and PARP [54] . Adamantane is the most common hydrophobic tag, [55] while Boc 3 Arg is another effective option that can also trigger proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism is that hydrophobic moiety induced protein of interest (POI) loses its original folded state and then recruits endogenous chaperone, [45] or hydrophobic moiety recognized by a chaperone, thereby mediating proteasomal degradation of the POI. [46] The HyT technique has proven to be highly efficient in its ability to specifically dismantle multiple targets, including the AR, [47] Her3, [48] Tau, [49] EZH2, [50] ALK, [51] CDK9, [52] CDK8, [53] and PARP. [54] Adamantane is the most common hydrophobic tag, [55] while Boc 3 Arg is another effective option that can also trigger proteolysis.…”
Section: Introductionmentioning
confidence: 99%